Assessment of the air quality of C.P. Garcia Avenue along the Institute of Civil Engineering (ICE) compound - Angeles, Eugene Jose L.; David, John Edzer L.
This study assesses the ambient air quality of C.P. Garcia Avenue along the Institute of Civil Engineering Compound. The air quality, particularly the Carbon Monoxide (CO), Nitrogen Dioxide (NO₂), and Particulate Matter 2.5 (PM 2.5) concentrations, are to be observed if they conform to the Philippine Clean Air Act of 1999 (R.A. 8749) for CO and NO₂, with DAO 2013-13 for PM 2.5. Data such as wind speed and direction, traffic speed, and traffic volume are correlated to determine the factors that greatly affect the ambient air quality. The concentrations of CO, and NO₂ are found to be compliant with the former being less than the set standard of 9 ppm per 8 hour averaging, and the latter being less than 80 ppm per 24 hour averaging. Different case is observed for PM 2.5 with concentrations reaching 0.058mg/NCM in February 16, and 0.087 mg/NCM for February 17 which is greater than 0.050 mg/NCM set standard.Pollutant transfer model and lag time methods are both used to derive regression equations relating traffic volume, traffic speed, and wind velocity with pollutant concentrations using multiple linear regression where the 10-minute lag regression model is developed for CO, the 30-minute lag regression model for NO₂, and no lag model for PM 2.5. Traffic volume, and speed are found to be significant variables since both values for all pollutants are less than 0.05 which shows there is significance after performing P-test at 95% confidence.